Springer handbook of materials data - Warlimont, Hans, 1931-; Martienssen, W. (Springer, 2018)
The second edition of this handbook is the most concise yet comprehensive compilation of materials data. The chapters provide succinct descriptions and summarize essential and reliable data for various types of materials. The information is amply illustrated with 1007 tables and 1110 figures selected primarily from well-established data collections.
Keywords: Materials -- Handbooks, manuals, etc.; Condensed matter -- Handbooks, manuals, etc.; elektronické knihy; electronic books